Women in Nigeria Labour Congress: a comparative study of the northern and southern regions - Ali, Mustapha Alhaji; Ahmad Zakuan, Ummu Atiyah; Ahmad, Mohammad Zaki (Center for Sustainabality Research & Consultancy, 2019)
The paper examined the position of women participation in NLC of Northern and the Southern regions and explored the mechanisms NLC put in place to empower women in the Northern and Southern regions of Nigeria.This paper is qualitative in nature. Data were obtained through the primary and secondary source of data collection. Contrast analysis approach was employed in comparing the position of women participation and empowerment in the NLC of the Northern and Southern regions of Nigeria. All data acquired were thematically analyzed using MAXQDA Software Version 2018. This paper is a Case study because it provides the researcher with an indepth understanding of the social phenomenon. Empowerment theory and the liberal feminist theory were used to explain the topic under study. This is because the postulations of these theories centered on equality between both genders in all societies. The study found that the position of women participation and empowerment in the NLC of the Northern region of Nigeria is low, because of patriarchal nature of the region, compared to the position of women participation and empowerment in NLC of the Southern region. It further added that women participation in the NLC of both regions is strong and healthy development.The paper recommended that women should be empowered educationally and allowed to hold managerial positions. It, in addition, suggested that parents and religious leaders should advise women from religious and parental points of view to participate actively in NLC of both regions.